RELIGIOUS TOLERANCE IN BANDA ACEH AND KEDIRI: CHALLENGES AND OPPORTUNITIES IN DIGITAL SPACE - Mawardi, Mawardi; Juwaini, Juwaini; Fazal, Khairil (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This research explores religious tolerance in Banda Aceh and Kediri within the context of digital space, focusing on the genealogy, contestation, and development directions of religious tolerance. The aim is to understand the social and cultural dynamics shaping patterns of religious tolerance in these regions and how digital spaces influence interfaith interactions. The methodology employed is a qualitative approach with case study methods, including in-depth interviews, social media content analysis, and participatory observation. The genealogy reveals fundamental differences between Banda Aceh, which exhibits a tolerance pattern influenced by Sharia law and strict norms, and Kediri, which is more inclusive due to its multicultural interactions. In digital spaces, religious contestation reflects tensions between conservative and progressive groups; Banda Aceh tends to uphold traditional values, while Kediri is more open to interfaith dialogue. The findings indicate that digital spaces have significant potential for fostering religious tolerance, though they are also vulnerable to hate speech and polarization. The future of religious tolerance in both regions will heavily depend on how communities and governments manage digital interactions, as well as educational efforts and policies that promote dialogue and interfaith understanding.